2005
DOI: 10.1093/tropej/fmi066
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Low Birthweight in Rural Bangladesh

Abstract: This study examines factors associated with low birthweight (LBW) in rural Bangladesh. Enrolled in early first trimester, 350 women were followed for duration of pregnancy and data gathered on maternal factors such as social, demographic, anthropometric, biochemical measures and newborn's birth weight within 48 hours of birth. Almost a quarter of babies (24%) were born with LBW and mean birth weight was 2961 g. Bivariate analysis found associations between LBW and mother's age, parity, weight and hemoglobin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 4 publications
2
28
0
2
Order By: Relevance
“…[34] The relationship between maternal hemoglobin level and birth weight was established in many studies and hemoglobin was identified as an important biomarker contributing to birth weight. [72836] In this study, information is lacking to ascertain when the hemoglobin levels were measured (e.g., during early or late pregnancy). Thus, it is not possible to draw any conclusion in relation to anemia level and LBW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] The relationship between maternal hemoglobin level and birth weight was established in many studies and hemoglobin was identified as an important biomarker contributing to birth weight. [72836] In this study, information is lacking to ascertain when the hemoglobin levels were measured (e.g., during early or late pregnancy). Thus, it is not possible to draw any conclusion in relation to anemia level and LBW.…”
Section: Discussionmentioning
confidence: 99%
“…[78910] In India, low body mass index (BMI), short stature, anemia and/or other micronutrient deficiencies are known to increase the risk of giving birth to a baby with LBW. [910] For example, low BMI is a reliable indicator for protein-energy malnutrition, which affects fetal growth during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Each year, an estimated 21 million infants are born with low birthweight worldwide, more than half of them are in South Asia (2). In Bangladesh, the incidence of low birthweight is estimated to be 22%, which is among the highest in the world (3), and in rural areas the estimates are as high as 31–47% (4). Low birthweight has two main causal components: preterm birth (<37 weeks of gestation) and intrauterine growth restriction (IUGR), which is commonly assessed as small for gestational age (<10 th percentile of the birthweight-for-gestational age sex-specific reference population) (3).…”
Section: Introductionmentioning
confidence: 99%
“…The Low birth weight levels in sub-Saharan Africa are found to be around 15% and Central and South America was about (10%). The low birth weights in the Caribbean are found to be around (14%) and almost as high as in sub-Saharan Africa [45,46]. A significant geographical variation that characterized the incidence of low birth weight in Europe, with lower rates in the more northerly countries is reported in recent study by Skokić et al [32].…”
Section: Discussionmentioning
confidence: 99%